The Relevance of Philosophy of Knowledge to Strengthening Digital Literacy and Students' Spiritual Values - Cukup Islamiarso; Lia Laili Rosadah; Yulia Wahyuni; Duski, Duski (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2026)
The development of globalization and digital transformation has fundamentally changed the way humans acquire, verify, and construct knowledge, including in the field of education. Advances in information technology encourage students to interact with various digital sources; however, they also present challenges such as disinformation, cognitive bias, and declining ethical awareness. These conditions highlight the importance of revitalizing the role of the philosophy of knowledge (epistemology) as a critical foundation for shaping students' rational, ethical, and spiritual thinking. This study aims to examine the relevance of the philosophy of knowledge in strengthening digital literacy and spiritual values in the global era. The research employs a qualitative approach through a literature study, exploring classical epistemological concepts such as rationalism, empiricism, and criticism, and connecting them to digital learning practices in schools. The findings reveal that the application of epistemological principles enhances reflective thinking, rationality, and moral responsibility in the use of technology. Furthermore, spiritual values such as intellectual honesty, awareness of truth, and gratitude for knowledge help strengthen students' character. Thus, the philosophy of knowledge plays a strategic role in balancing digital intelligence with spiritual depth among students.